How is the ‘Problem’ of Employment for Disabled People Represented in New Zealand Government Policy? A Post-structural Discourse Analysis - Joanna Fadyl; Mariya Khoronzhevych (SAGE Open)
Disabled people have persistently lower employment than non-disabled, and disability scholarship has analysed the ways in which the social construction of ‘work’ participates in the marginalization of disabled people. Disability-related hiring, workplace practices and labour organisation are often influenced by goverment policy. This article reports on a post-structural discourse analysis of disability employment policies in New Zealand, analysing how these policies represent employment issues for disabled people. Findings show that despite employing language that reflects social understandings of disability, policies reproduce discourses that view disability as a limitation of the body rather than a social construct shaped by environmental factors. Paid employment was constructed as crucial for full participation in society, positioning unemployed disabled people as missing out on full citizenship. The policies construct employers as central to addressing underemployment of disabled people, but overlook ongoing systemic discrimination, focusing on information as a strategy to achieve inclusive employment practices. While these policies emphasise inclusion, they often neglect to challenge the organisation of work itself, positioning disabled people as needing to adapt to pre-existing work structures, without considering broader systemic reforms that go beyond just inclusion of disabled people in work structures that have persistently excluded them.